Analisis Pengaruh Konsumsi Rumah Tangga, Investasi dan Pengeluaran Pemerintah Terhadap Pertumbuhan Ekonomi Papua Barat Tahun 2012 - 2016 (Studi Kasus 4 Kabupaten 1 Kota) - Gerardus Raditya Yoga Putra; Elina Relawaty Situmorang; Ketysia Imelda Tewernussa (Lensa Ekonomi, 2021)
This study aims to explain the household consumption influence, investment, and government spending on economic growth in West Papua Province (case studies: 4 regency and 1 city) in 2012-2016. The data obtained from relevant agencies were Central Bureau of Statistic (BPS), Representative Office of Directorate General Treasury of Finance Ministry, and BPMP2T (Investment Agencies and Integrated Service Center) in West Papua Province. The result of household consumption variable (X1) and investment variable (X2) positively and significantly influence to economic growth variable (Y) in five regencies/cities in West Papua Province. However, government spending variable (X3) does not influence positively and significantly to the economic growth (Y) in five regencies/cities in West Papua Province. Penelitian ini bertujuan untuk menjelaskan pengaruh konsumsi rumah tangga, investasi, dan pengeluaran pemerintah terhadap pertumbuhan ekonomi di Provinsi Papua Barat (studi kasus: 4 kabupaten dan 1 kota) tahun 2012-2016. Data diperoleh dari instansi terkait yaitu Badan Pusat Statistik (BPS), Kantor Perwakilan Ditjen Perbendaharaan Kementerian Keuangan, dan BPMP2T (Badan Penanaman Modal dan Pusat Pelayanan Terpadu) di Provinsi Papua Barat. Hasil penelitian variabel konsumsi rumah tangga (X1) dan variabel investasi (X2) berpengaruh positif dan signifikan terhadap variabel pertumbuhan ekonomi (Y) di lima kabupaten/kota di Provinsi Papua Barat. Namun variabel pengeluaran pemerintah (X3) tidak berpengaruh.